Molecular characterisation and phylogenetic analysis of Marek's disease virus in Turkish layer chickens. Issue 5 (2nd September 2020) - Yilmaz, A.; Turan, N.; Bayraktar, E.; Tali, H. E.; Aydin, O.; Umar, S.; Cakan, B.; Sadeyen, J.-R.; Baigent, S.; Iqbal, M.; Nair, V.; Yilmaz, H.
ABSTRACT: 1. There is no current data about the genotypes of Marek's disease virus (MDV) in Turkish poultry flocks; hence, this study was performed to analyse CVI988/Rispens, turkey herpesvirus (HVT) vaccine viruses and MDV field viruses as well as to perform phylogenetic analysis of MDV in Turkish layer chickens. 2. In 2017 and 2018, a total of 602 spleen samples from 49 layer flocks were collected from the Marmara, West Black Sea and Aegean regions. DNA was extracted from the spleen samples and the samples were analysed by real-time PCR probe assay to detect CVI988/Rispens and HVT vaccine viruses and MDV field strains. Samples found positive for MDV by real-time PCR were subjected to PCR using the Meq gene primers for phylogenetic analysis. 3. Amongst 49 flocks, virulent MDV was detected in nine flocks. CVI988/Rispens and HVT vaccine strains were detected in 47 flocks and HVT in all 49 flocks. Splenomegaly, hepatomegaly and tumours in the oviduct were observed in chickens of affected flocks. Virulent MDV was detected in 120 out of 602 spleen samples. Sequencing and phylogenetic analyses showed that MDVs detected in this study were closely related to MDV strains from Italy, Poland, Saudi Arabia, Iraq, India and China but showed diversity with MDV strains from Egypt and Hungary. Multiple sequence analysis of the Meq protein revealed several point mutations in deduced amino acid sequences. Interestingly, CVI988/Rispens vaccine virus from China (AF493555) showed mutations at position 66 (G66R) and 71 (S66A) along with two other vaccine strains from China (GU354326.1) and Russia (EU032468.1), in comparison with the other vaccine strain CVI988/Rispens (DQ534538). The molecular analyses of the Meq gene suggested that Turkish field strains of MDV are in the class of virulent or very virulent pathotypes. 4. The results have shown that MDV still affects poultry health, and the phylogenetic and amino acid variation data obtained will help in vaccination and control strategies.